Capitalismo tardio e educação profissional : as escolas agrotécnicas federais mineiras de Barbacena, Rio Pomba e Uberlândia (1940-1970) - Coutinho, Ednaldo Gonçalves (2012)
This research aimed at salvaging the history of creation of three school institutions from Minas Gerais State (Brazil), as far as history, capitalism and education are concerned, focusing on the Professional Education, mainly for the Agricultural Teaching: Uberlândia Campus, belonging to the Federal Institute of Education, Science and Technology of Triângulo Mineiro (previously named Uberlândia Agricultural School and Federal Agrotechnical School of Uberlândia) and Rio Pomba Campus (previously named Rio Pomba Agricultural School, Agricultural Gymnasium of Rio Pomba and Federal Center of Technological Education of Rio Pomba) and the one of Barbacena (once named Barbacena Agricultural school, Agricultural School of Barbacena and Agrotechnical Federal School of Barbacena), which belong to the Federal Institute of Education, Science and Technology of the Southest of Minas Gerais. Its objectives were the following: a) understand what motivated the creation of these institutions in the countryside of Minas Gerais State, in terms of education policies and its relations to the national economy aimed at the agricultural sector; b) understand if the pedagogical practices of the Agricultural School were in accordance with the desired aim , considering its foundation, and if they were in consonance with the laws; c) investigate if the formation of the Agricultural or Farming Technician, offered by these institutions, has been in accordance with the Agricultural modernization during the researched period and if this formation was accomplished in and to this modernization desired by the Federal Government; d) analyze its curricular structures and verify if they were all identical; e) evaluate which social class it was aimed at. In order to carry out this investigation, a sinuous methodological way was used to comprehend a bibliographic review of the most adequate themes to the research and the analysis of oral, iconographic and written sources. As theoretical support, we can highlight the contributions of Magalhães (2004), Faria Filho (2003), Werle (2004), Fonseca (1961a; 1961b), Cunha (1979a; 1979b; 1983; 1984; 2000a; 2000b; 2000c; 2001), Ianni (1996), Prado Júnior (1967), Ramos (1995), Romanelli (1998), which are already considered acknowledged studies by the Brazilian traditional, technical and professional education, mainly, in the context of its public policies and the critical appreciation of the composition of this chain of institutions in the national scenario. In their historic trajectory, the searched schools experienced a series of transformations which, in the superficiality of the legal texts, were conducted for administrative reasons, but which, under a hermeneutic point of view, were deliberated transformations to meet economic issues. The acknowledgement that the economy and the political interests determined the routes of Education in Brazil, becomes even more obvious when, in the modernization context, the School-Farm System was implanted, according to which pedagogical practice and the production in economical conditions are confused and direct the formation of the technician to act as an agent of modernization. The used sources (public and institutional archives, local newspapers, Town-hall minutes, pictures, bibliographical mapping, etc) enabled the analyzes and the comprehension of the facts and educational discussions in national and regional levels and permitted to confront them with those described by the specialized literature to the Brazilian reality. Finally, the thesis establishes a dialog with historic and theoretical bases and also search for interrelations with Brazilian Education issues, mainly, the ones which refer to Agricultural teaching.